A Study on Trend of the Income Inequality: Evidence from Bangladesh - Biswas, Shyamapada; Rahman, Ataur; Shinwary, Salman Salem (Indian Journal of Finance, 2012)
This paper seeks to unfold the relationship between income inequality, poverty and economic growth in Bangladesh for the period 1974 - 2006. For the measurement of the income inequality, Gini Coefficient has been used. For analyzing the overall trend in the income inequality national, urban and rural, Gini Coefficients from 1974 to 2006 have been investigated. The trend in national, urban and rural Gini Coefficients express the state of national, urban and rural income inequality and poverty. With the aim of examining the correlations among income inequality, poverty and growth of the economy, correlations and coefficient of regressions among the growth of the GDP, national, urban and rural Gini Coefficients have been computed and analyzed. Finally, validating the findings of the data analysis opinion survey has been done. In the end, on the basis of findings of the study suggestions for the reduction of the income inequality and poverty have been made.